1993
DOI: 10.1073/pnas.90.12.5848
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear progesterone receptor is mainly heat shock protein 90-free in vivo.

Abstract: Heat shock protein 90 (hsp90) is associated with many steroid receptors in tissue homogenates. It is widely accepted that hsp90 regulates the binding of the receptor to the corresponding gene regulatory element. However there is no unequivocal evidence that steroid receptor-hsp90 complexes are present in the intact cells. We demonstrate here the absence of progesterone receptor (PR)-hsp90 complexes in intact target cell nuclei, using immunohistochemical and biochemical methods to determine the location and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…In fact, a hsp90-containing 8S progesterone receptor complex has been obtained from purified nuclei of rabbit uterus in the absence of the cognate hormone (23). On the other hand, the reported conclusion that the nuclear progesterone receptor is mainly hsp90-free (24) seems to be due to the inability to detect the small fraction of the abundant cytoplasmic hsp9O that would be colocalized in nuclei with PR. Here we were able to demonstrate that some 9OWT, when cotransfected with rPR, is localized in the nucleus.…”
Section: Several Important Deductions Stem From These Results (I)mentioning
confidence: 95%
“…In fact, a hsp90-containing 8S progesterone receptor complex has been obtained from purified nuclei of rabbit uterus in the absence of the cognate hormone (23). On the other hand, the reported conclusion that the nuclear progesterone receptor is mainly hsp90-free (24) seems to be due to the inability to detect the small fraction of the abundant cytoplasmic hsp9O that would be colocalized in nuclei with PR. Here we were able to demonstrate that some 9OWT, when cotransfected with rPR, is localized in the nucleus.…”
Section: Several Important Deductions Stem From These Results (I)mentioning
confidence: 95%
“…The direct interaction between hMR and Factin cannot be extended to other steroid receptors. Indeed, GR interacts with F-actin via hsp90, while both progesterone [27,28] and estrogen receptors [29,30] are nuclear, and F-actin is mainly cytoplasmic.…”
Section: Discussionmentioning
confidence: 99%
“…Since p23 and the immunphilins are though to be associated with the complex through the Hsp90, it is most probably the latter which is responsible for masking the αD epitope. In a previous immunohistochemical study, we showed that αD can recognize endogenous PR in the nucleus of chicken oviduct cells, indicating that the epitope is readily accessible, and furthermore, that most of the PR molecules in the cell nucleus are in dissociated form [Tuohimaa et al 1993]. In addition, we have previously shown that fixation does not cause artificial exposure of the epitope [Pekki and Tuohimaa 1989].…”
Section: Discussionmentioning
confidence: 91%
“…There is evidence that Hsp90 is a cytoplasmic protein and that there is not a sufficient amount of Hsp90 molecules in the nucleus to form complexes with nuclear steroid receptors [Tuohimaa et al 1993].There is, however, evidence that the glucocorticoid receptor (GR), which is predominantly cytoplasmic in its unoccupied form, can be crosslinked in vivo with Hsp90, which would imply that steroid receptors may be associated with Hsp90 in the cytoplasmic compartment. [Rexin et al 1991].…”
Section: ©2003 European Journal Of Histochemistrymentioning
confidence: 99%
See 1 more Smart Citation